2017
DOI: 10.1155/2017/5480562
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Lichen Planus: Understanding a Potentially Severe Stricturing Disease

Abstract: A 67-year-old woman with a long-standing history of recurrent dysphagia and esophageal strictures failed to respond to aggressive antireflux management. She required multiple dilations for symptomatic strictures that were discovered throughout the esophagus. Intralesional, topical, and systemic glucocorticoid therapies were utilized without resolution in symptoms. Several years after initial presentation, histopathology ultimately demonstrated lichenoid features and a diagnosis of esophageal lichen planus (ELP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
0
15
0
3
Order By: Relevance
“…Due to its rare nature, there is a paucity of data investigating ELP, and our understanding of the disease is mainly derived from case reports and case series. The most common presenting symptom is dysphagia, though some patients may also experience odynophagia and many are asymptomatic 3 5–8. A review of 72 cases of ELP performed by Fox et al showed that 99% of this cohort had extraoesophageal manifestations of lichen planus, most often oral (89%), vulvovaginal/anogential (42%) and cutaneous (38%) 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its rare nature, there is a paucity of data investigating ELP, and our understanding of the disease is mainly derived from case reports and case series. The most common presenting symptom is dysphagia, though some patients may also experience odynophagia and many are asymptomatic 3 5–8. A review of 72 cases of ELP performed by Fox et al showed that 99% of this cohort had extraoesophageal manifestations of lichen planus, most often oral (89%), vulvovaginal/anogential (42%) and cutaneous (38%) 5.…”
Section: Discussionmentioning
confidence: 99%
“…Data show that the majority of ELP involves the proximal third of the oesophagus 5. Histopathology is very important in making a diagnosis, and the presence of Civatte bodies, necrotic keratinocytes that appear eosinophilic on light microscopy, is confirmatory for ELP 3–8. Direct immunofluorescence can be used if histology is inconclusive 9.…”
Section: Discussionmentioning
confidence: 99%
“…The disorder predominantly involves middle-aged to elderly women (approximately 87% of women with a median age of 61.9 years. 6 Dysphagia is the most common symptom followed by odynophagia and food impaction. 4,6 EGD plays a diagnostic and therapeutic role in these patients and should be performed in all patients with LP and GI symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…6 Dysphagia is the most common symptom followed by odynophagia and food impaction. 4,6 EGD plays a diagnostic and therapeutic role in these patients and should be performed in all patients with LP and GI symptoms. Macroscopic findings are non-specific but include ulcers, erosions, stricture formation, whitish papules, esophageal pseudomembranes as well as inflamed and friable mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation